Konsep Murabbi dalam Al-Qur’an dan Hadits: Analisis Peran Pendidik dalam Pendidikan Islam - Mufaizah Mufaizah; Wardatus Sholikha; Ajeng Putri Wulandari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2023)
The motivation for this study is the importance of the role of murabbis as educators in Islamic education based on the values of the Qur'an and Hadith. The goal of this study is to analyze the concepts of murabbis and the role of educators in shaping the character and intellect of students according to Islamic teachings. This study also suggests further studies on the practical implementation of Islamic teachings in schools